The effects of organization context on knowledge exploration and exploitation - Gonzalez, Rodrigo Valio Dominguez; de Melo, Tatiana Massaroli [UNESP] (Elsevier, 2018)
The knowledge-based view of the firm points knowledge as the main resource able of generating competitive advantage for organization. This competitive advantage is the result of the innovative process, which requires knowledge exploration and exploitation. Several studies have aimed to analyze factors that support the knowledge management (KM) process and generate taxonomies related to the practice of KM. However, there is a gap in the literature on organizational knowledge regarding the relationship of contextual factors with the knowledge exploration and exploitation process as well as with the generating of a typology that considers these two processes. To achieve this goal, this study uses a quantitative approach, based on a survey with 234 companies in the automotive industry. Our results show that the knowledge exploration and exploitation process are differently impacted by five contextual factors considered in this research - human resources management, supportive leadership, learning culture, autonomy and systems of information technology (IT). While exploration is more impacted by learning culture, autonomy and IT systems, exploitation is more associated with supportive leadership and learning culture. Considering innovation for knowledge exploration and exploitation and contextual factors, this research also identifies three clusters in the automotive industry, named innovative companies, exploitative companies and passive companies.
Keywords: Autonomy; Human resource management; Innovation; Knowledge exploration and exploitation; Leadership; Learning culture